Scaling up - From Vision to Large-Scale Change - A Management Framewor k for Practitioners - Cooley, Larry; Kohl, Richard; Ved, Rajani R. (MSI, 2016)
This document was originally published in 2006 and re-issued in a subs tantially revised Second Edition in 2012.